Assessment of social effectiveness of investments in the hospitality business of Ukraine - Liudmila Bovsh; Larysa Hopkalo; Rostom Beridze; Alla Okhrimenko (Public and Municipal Finance, 2020)
Nowadays, the investment flows define the prospects of development of the economic system of any level, as they give the innovative opportunities and are the instrument of compliance in the financial and legal field. Taking into account the significant resource potential of the Ukraine, it is important to study the industries-catalysts, able to mobilize the financial resources, to activate the development of infrastructure and to become an impetus for the development of the specific location and the regions as a whole, which a priori stimulates meeting the social needs. This study aims to analyze the parameters of social effectiveness of investments in the hospitality business, which creates the multiplicative effect in the territories’ development systems, involving many related industries, which are the donors for territorial communities financing, in the creation of the concept-product. As a weighty proportion in the territorial community’s GDP, the usefulness of the investments in the hospitality was analyzed through the lens of sociality, which nowadays acquires the signs of non-material asset in implementing the projects, as it ensures the communicative and information interaction, harmonizes the relationship between the investors, recipients of investments, local territorial community, and society.